2020
DOI: 10.3389/fpsyt.2020.00598
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Transcranial Direct Current Stimulation on Substance and Food Craving: What Effect Do Modulators Have?

Abstract: Substance addiction and food addiction are significant social problems worldwide. In previous studies of substance addiction, transcranial direct current stimulation (tDCS) has been used to influence craving of substance or food. However, the reported effects are not always consistent due to inconsistent experimental settings. The way modulators influence the effect of tDCS on substance addiction is worth exploring. This meta-analysis was conducted to estimate the effect size of tDCS on substance and food crav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 97 publications
7
25
0
Order By: Relevance
“…This suggests that tDCS might decrease the rate of relapse in abstinent alcohol-dependent patients. This is similar to what is observed in humans 19 , 77 , 78 . The amount of ethanol intake per session was noticeably higher in sham animals during the first week of reacquisition than in the last week of the training sessions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that tDCS might decrease the rate of relapse in abstinent alcohol-dependent patients. This is similar to what is observed in humans 19 , 77 , 78 . The amount of ethanol intake per session was noticeably higher in sham animals during the first week of reacquisition than in the last week of the training sessions.…”
Section: Discussionsupporting
confidence: 91%
“…Recent meta-analyses have provided additional evidence that tDCS over the DLPFC reduces craving and ethanol consumption. Interestingly, larger effects were found with repeated stimulations than with single stimulation 77 , 78 , and a level B (possible efficacy) recommendation has been proposed for tDCS in addiction/craving 79 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies showing a diminished craving for sweet foods included mostly participants with either frequent food craving [102][103][104], BED or subBED [99], thus demonstrating a study population that exhibits dysregulated eating behaviors. A recently published meta-analysis evaluated the effects of modulators in tDCS studies on food and substance craving and concluded that the stimulation site (anodal left or right DLPFC) and current intensity (1 or 2 mA) do not influence tDCS outcomes [123]. However, stimulation duration made a significant difference, meaning that a longer total stimulation time was associated with a stronger craving reduction [123].…”
Section: Tdcs Effects On Food Craving and Desire To Eatmentioning
confidence: 99%
“…Multiple studies showed that both single and multiple sessions of DLPFC stimulation reduced craving in crack [35], marijuana [36], heroin [37], alcohol [38], methamphetamine [39], and nicotine [40] use disorders. However, there have been other tES studies that reported no significant differences between active and sham groups in terms of self-reported drug craving (see this systematic review [41] and this meta-analysis [42]). The neural substrate of the mechanism of action leading to various effects and how to optimize stimulation montage by targeting networks known to be dysregulated in SUDs are not clear yet [43,44].…”
Section: Introductionmentioning
confidence: 75%